1995
DOI: 10.1002/jso.2930590305
|View full text |Cite
|
Sign up to set email alerts
|

Malignant germ cell tumors of the ovary: A study of 20 cases

Abstract: In a study of 20 patients diagnosed with malignant ovarian germ cell tumors between 1961 and 1993, clinical and pathologic findings were evaluated. Of the 20 patients, seven (35%) had dysgerminoma, two (10%) endodermal sinus tumor, three (15%) malignant teratoma, one (5%) malignant struma ovarii, one (5%) primary ovarian carcinoid, two (10%) benign teratoma with malignant transformation, and four (20%) combination germ cell tumor. Twelve patients (60%) had stage IA, five (25%) stage IC, and three (15%) stage I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…This has been shown to be feasible at all stages of the disease (13,14). Successful pregnancy has been reported even after treatment of bilateral ovarian dysgerminoma (15).…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown to be feasible at all stages of the disease (13,14). Successful pregnancy has been reported even after treatment of bilateral ovarian dysgerminoma (15).…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that for young women who wish to preserve child-beariung capacity, regardless of the stage of tumour, fertility preserving surgery with complete surgical staging followed, if necessary by cisplatin-based combination chemotherapy is an appropriate and defi nite treatment in the absence of involvement of the contralateral ovary and uterus. For patients in whom child -bearing capacity is not an issue, surgery should include abdominal hysterectomy and salphin go opherectomy with complete staging, followed if necessary by chemotherapy 13 . Of the non neoplastic lesions follicular cysts and corpus luteal cysts were commonest (80%) 14 .…”
Section: Resultsmentioning
confidence: 99%
“…After the Cisplatin-based combination chemotherapy regimens such as BEP have improved survival rates for germ cell tumors, including YST, 4 and recently, BEP regimens have been established as an effective treatment for YST, with complete remission and cure rates of 80%-90%. 5 The chance of complete recovery now approaches 100% for early-stage patients and at least 75% for more advanced-stage patients. 6 Three courses of BEP is the current standard postoperative adjuvant chemotherapy regimen for female patients with YST with no or small-volume residual tumor after primary surgery, and four courses of BEP is recommended in cases of bulky residual disease after surgery.…”
Section: Discussionmentioning
confidence: 99%